2020
DOI: 10.31111/nsnr/2020.54.2.537
|View full text |Cite
|
Sign up to set email alerts
|

New cryptogamic records. 6

Abstract: First records of chrysophytes for the North-Western Russia and the Leningrad Region, fungi for the Pskov Region, lichens for Svalbard and the Altai Territory, bryophytes for the Far East, Arkhangelsk, Saratov, Voronezh and Sakhalin regions, the Karachayevo-Circassian Republic, Republic of North Ossetia – Alania, the Republic of Altai, the New Siberian Islands Archipelago, the Kuril Islands, the Republic of South Ossetia. The data on its localities, habitats and distribution are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Knowledge on the lichens of Horsnund, Bockfjorden, Sørkapp Land, Edgeøya and several other parts of Svalbard was supplemented successively by: Hafellner (1982), Elvebakk (1984a), Nimis (1985), Olech (1987, Olech and Alstrup (1989), Aptroot and Alstrup (1991), Elvebakk and Tønsberg (1992), Schuhwerk (1992), Øvstedal et al (2009), Redchenko et al (2010), Konoreva (2011), Singh and Ravindra (2013), , , Wietrzyk et al (2016Wietrzyk et al ( , 2017, , Chesnokov (2018, 2021), , , , and Czernyadjeva et al (2020). Finally, Øvstedal et al (2009) reported 742 species from Svalbard, but only 34 species from Barentsøya.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge on the lichens of Horsnund, Bockfjorden, Sørkapp Land, Edgeøya and several other parts of Svalbard was supplemented successively by: Hafellner (1982), Elvebakk (1984a), Nimis (1985), Olech (1987, Olech and Alstrup (1989), Aptroot and Alstrup (1991), Elvebakk and Tønsberg (1992), Schuhwerk (1992), Øvstedal et al (2009), Redchenko et al (2010), Konoreva (2011), Singh and Ravindra (2013), , , Wietrzyk et al (2016Wietrzyk et al ( , 2017, , Chesnokov (2018, 2021), , , , and Czernyadjeva et al (2020). Finally, Øvstedal et al (2009) reported 742 species from Svalbard, but only 34 species from Barentsøya.…”
Section: Introductionmentioning
confidence: 99%